SPAWNING BIOLOGY OF MYSTVS GULIO IN LAKE PULICAT, INDIA - Kaliyamurthy, M (Indian Journal of Fisheries, 2011)
Observations made on the length-weight relationship and some aspects of the spawning biology of Mystus gulio are gives. This species was observed to breed during August-October in Lake Pulicat. The fecundity was found to vary from •1,283 to 24,768 in the fish of size range, 8<M28 mm. One g of ovary was found to contain on an average 4,089 ova and the fecundity factor was calculated to be 244.